THE USE OF TEACHER-MADE YOUTUBE VIDEOS IN VIRTUAL WRITING LEARNING: STUDENTS’ PERCEPTIONS - Rohmawati, Anisatur; Asmara, Candra Hadi (Universitas Suryakancana, 2022)
The research objectives were to find answers the perceive also interests Thai EFL students towards teacher-made YouTube videos when learning writing virtually. Thirty students from grade 5 at Ban Nonkokkha School, Loei, Thailand, participated. The method used in this research was mixed methods research with explanatory design type. The researcher collected quantitative data by distributing questionnaires earlier then implemented the qualitative data by conducting interviews to add more reliable results. The researcher analyzed the data obtained from the questionnaire were analyzed using a Likert scale calculation by frequency of the responses received by students expressed in percentages and then explained from the results of interviews. From quantitative and qualitative analysis, it is known that most students agree in virtual writing learning through teacher-made YouTube videos. The findings also showed the teacher-made YouTube videos make learning more enjoyable, make learning English easier, know English words better, and encourage the students to learn English even aside from class. Moreover, they can also learn how to write the correct sentences. Meanwhile, the study results also showed that some students find it difficult when virtual learning takes place. Some of them had low vocabulary mastery problems and poor internet signal.